Hepatitis B Virus Revaccination With Standard Versus Pre-S Vaccine in Previously Immunized Patients With Celiac Disease. Issue 4 (October 2015) - Heshin-Bekenstein, Merav; Turner, Dan; Shamir, Raanan; Bar-Meir, Maskit; Dagan, Ron; Zevit, Noam; Silbermintz, Ari
ABSTRACT: Objective: Previous studies have suggested that hepatitis B virus (HBV) vaccines may be less immunogenic in individuals with celiac disease (CD). A pre-S vaccine (Sci-B-Vac) has demonstrated superior immunogenicity compared with standard HBV vaccines in several diseases. We compared the short-term immunogenicity of a pre-S vaccine with a HBV vaccine (Engerix B) for repeat vaccination of seronegative, previously immunized patients with CD. Methods: Participants were 1 to 18-year-old children with CD who despite standard HBV vaccines in infancy had nonprotective hepatitis B surface antibody (HBs-Ab) concentrations (⩽10 mIU/mL). Patients were randomized to receive either Engerix B or pre-S vaccine. HBs-Ab concentrations were measured 1 month after the first dose. For those who had not responded after 1 dose, measurement was repeated after the third dose. Results: Children (n = 82) were analyzed (42 pre-S vaccine and 40 Engerix B). Baseline characteristics were similar for both groups, including gluten-free diet status. Both arms showed high response rates following the first injection: 41 (98%) versus 35 (87%) for pre-S vaccine and Engerix B recipients, respectively ( P = 0.08). All other patients responded when measured after dose 3. HBs-Ab concentrations (mIU/mL) were higher in the pre-S vaccine group (median 925, interquartile range [IQR] 424–1000) than the Engerix B group (median 363, IQR 106–996, P = 0.005). Twenty (48%) of the pre-S vaccine recipients were "high responders" (>1000 mIU/mL) versus 10 (25%) in Engerix B recipients ( P = 0.008). Conclusions: Both vaccines elicited adequate booster responses in most previously vaccinated patients with CD with nonprotective HBs-Ab concentrations. Pre-S vaccine administration resulted in higher Hbs-Ab concentrations. Our data suggest that a single dose of either vaccine is sufficient to raise titers to protective levels in most patients with CD.